Pattern of Functional TTX-Resistant Sodium Channels Reveals a Developmental Stage of Human iPSC- and ESC-Derived Nociceptors - Eberhardt, Esther; Havlicek, Steven; Schmidt, Diana; Link, Andrea; Neacsu, Cristian; Kohl, Zacharias; Hampl, Martin; Kist, Andreas; Klinger, Alexandra; Nau, Carla; Schüttler, Jürgen; Alzheimer, Christian; et al. (Stem Cell Reports, 2015)
Human pluripotent stem cells (hPSCs) offer the opportunity to generate neuronal cells, including nociceptors. Using a chemical-based approach, we generated nociceptive sensory neurons from HUES6 embryonic stem cells and retrovirally reprogrammed induced hPSCs derived from fibroblasts. The nociceptive neurons expressed respective markers and showed tetrodotoxin-sensitive (TTXs) and -resistant (TTXr) voltage-gated sodium currents in patch-clamp experiments. In contrast to their counterparts from rodent dorsal root ganglia, TTXr currents of hPSC-derived nociceptors unexpectedly displayed a significantly more hyperpolarized voltage dependence of activation and fast inactivation. This apparent discrepancy is most likely due to a substantial expression of the developmentally important sodium channel NAV1.5. In view of the obstacles to recapitulate neuropathic pain in animal models, our data advance hPSC-derived nociceptors as a better model to study developmental and pathogenetic processes in human nociceptive neurons and to develop more specific small molecules to attenuate pain.
EVALuna2:2465